Facets of adult attachment style in patients with obsessive-compulsive disorder. (December 2021) - Pozza, Andrea; Dèttore, Davide; Marazziti, Donatella; Doron, Guy; Barcaccia, Barbara; Pallini, Susanna
Abstract: Literature data did not show univocal evidence in discriminating which form of attachment insecurity is involved in obsessive-compulsive disorder (OCD): both anxiety and avoidance was related to OCD symptomatology. No study used the Attachment Style Questionnaire (ASQ) that allows for investigation of differentiated facets of attachment anxiety and of avoidance. We investigated: (1) whether individuals with OCD differed from controls in the facets of attachment security (anxiety and avoidance), (2) which attachment facets predicted a diagnosis of OCD, controlling for socio-demographics and obsessive beliefs, (3) which attachment facets predicted specific OCD symptoms, controlling for socio-demographics and obsessive beliefs. Two hundred seventy participants (135 OCD patients and 135 matched controls) completed the Obsessive-Compulsive Inventory-Revised, Obsessive Beliefs Questionnaire-46 and ASQ. OCD patients reported respectively lower and higher levels on confidence and attachment anxiety than controls. Higher need of approval was the most important predictor of OCD diagnosis beyond the other attachment facets, and even of the obsessive beliefs. Using multivariate generalised linear models, the two facets of attachment anxiety, the need for approval (that predicted higher levels of obsessing and ordering symptoms), and preoccupation with relationships (that predicted higher hoarding symptoms) seemed to explain variance over and above OCD-related beliefs and socio-demographics. Discomfort with closeness contributed to the predictions of ordering symptoms. In conclusion, the interpersonal dynamics related to attachment in OCD patients should be carefully considered during assessment and treatment of OCD patients in clinical practice.